Nasolacrimal System Fractures: A Description of Radiologic Findings and Associated Outcomes. Issue 4 (October 2015) - Garg, Ravi K.; Hartman, Michael J.; Lucarelli, Mark J.; Leverson, Glen; Afifi, Ahmed M.; Gentry, Lindell R.
Abstract : Background: Fractures of the bony nasolacrimal system (NLS), including the lacrimal sac fossa and nasolacrimal canal, have not been comprehensively described in patients with facial trauma. Characterization of these injuries may help facial trauma surgeons better predict which patients will develop lacrimal outflow obstruction symptoms including epiphora and dacryocystitis and who may eventually need lacrimal surgery. Methods: CT images for all patients seen at the University of Wisconsin Hospital and Clinics for craniofacial trauma were reviewed from January 2001 to December 2005. Patients were included if they had a NLS fracture and at least 1 year of follow-up. Fracture patterns were described and correlated with clinical outcomes documented in the medical record. Outcomes, including the development of epiphora or dacryocystitis and the need for lacrimal surgery, were analyzed using Fisher exact test. Results: We identified 104 patients with NLS fractures among 1980 patients with craniofacial trauma who had at least 1 year of follow-up. Eleven patients (10.6%) developed epiphora or dacryocystitis, and 2 patients (1.9%) required dacryocystorhinostomy (DCR). Ten radiographic injury patterns were characterized. Avulsion of the lacrimal crest, bone fragment in the lacrimal sac fossa or duct, duct compression greater than 50%, and nasomaxillary buttress displacement were significantly associated with the development of epiphora or dacryocystitis ( P < 0.05). Nasomaxillary buttress displacement was significantly associated with the eventual need for DCR ( P = 0.03). Conclusions: Patients with radiographic evidence of NLS fracture have an approximately 10% risk of developing epiphora or dacryocystitis. We describe 5 NLS fracture findings that are significantly associated with the development of lacrimal outflow obstruction. The presence of nasomaxillary buttress fracture and displacement suggests a significantly higher risk of eventually needing lacrimal surgery.